Developing Natural Literacy In Primary Grades - Yunusova Diloromkhan (Genius Journals, 2024)
This research paper examines the development of nature literacy in primary schools as a means of fostering environmental awareness and scientific curiosity in young learners. By integrating nature-based learning experiences into early education, teachers can foster a deeper appreciation of the natural world, instill values of sustainability, and foster applied scientific inquiry. Through a multidisciplinary approach that integrates science, ecology, and outdoor education, this paper highlights the importance of nature literacy in developing environmentally conscious and scientifically literate individuals from a young age
Keywords: Nature literacy; Primary education; Nature-based education; Environmental awareness